Cost Efficiency Analysis of Broiler Production in Peninsular Malaysia - Mohammad Nor, N. A. A.; Buda, M.; Mohd Nor, N.; Wong, K. S. K.; Sharifuddin, J.; Suhaimee, S. (Tropical Animal Science Journal, 2024)
The broiler industry is crucial in Malaysia’s agricultural sector, contributing significantly to meat production and the economy. However, the industry faces significant challenges, primarily stemming from high production costs, with feed costs constituting a substantial portion. Therefore, there is a need to improve domestic farm performance and competitiveness by optimizing resources and minimizing expenses to enhance overall productivity. This study aims to estimate the extent of cost efficiency in broiler farming in Peninsular Malaysia and identify key determinants influencing the inefficiency cost. A comprehensive survey involving 241 broiler farms in Peninsular Malaysia was conducted using structured questionnaires and a stratified random sampling technique. Employing the Stochastic Cost Frontier model revealed an operational inefficiency of approximately 5.7% above optimal costs among the surveyed farms, indicating substantial potential for a 5.7% reduction in production costs through enhanced management strategies. Factors such as feed prices, day-old chick prices, price of miscellaneous inputs, production output levels, and capital investment prices emerged as prominent influencers in the broiler cost function. Furthermore, the study indicated that socio-economic factors such as housing system, extension visits, credit access and contract farming are associated with lower inefficiencies, thereby enhancing cost efficiency in broiler farming operations. Conversely, higher bird mortality rates are associated with the increased inefficiency. Gaining insights into these factors is crucial for stakeholders to allocate resources wisely, plan strategically, and enhance competitiveness in broiler farming.